The drivers of a superior's trust formation in his subordinate: The manager–management accountant example. Issue 4 (7th November 2016) - Nitzl, Christian; Hirsch, Bernhard
Abstract : Purpose: Because of the importance of accounting information to a manager's decision-making process, his/her working relationship with his/her supporting management accountant is used as a paradigm of a superior-subordinate working relationship. This paper aims to analyze the drivers of trust in this relationship. Design/methodology/approach: Based on responses from 446 managers, the authors tested a structural equation model for various trust drivers. Findings: The authors found that when management accounting generally has a powerful role in a company, it positively affects the manager's perceptions of his subordinate's trustworthiness. Although the absolute level of trust remains stable over time, the influences of the bases of the trust change significantly. Over the long run, perceived trustworthiness fully mediates other trust factors, such as the manager's trust disposition and the organizational setting, which highlights the importance of the individual trust relationship even for strong and functional superior–subordinate relationships. Research limitations/implications: Consistent with other studies, the results contain the classic limitations of survey studies. This study investigates the drivers of trust and provides insights into the trust relationship between managers and management accountants. Future studies should verify these findings for other important work relationships. Originality/value: Trust research has typically focused only indirectly on the relevance of the trust that a superior has in his supporting subordinate. The authors show how these trust drivers intertwine and how their influences shift over time.